2021
DOI: 10.1186/s12943-021-01365-z
|View full text |Cite
|
Sign up to set email alerts
|

The role and application of small extracellular vesicles in gastric cancer

Abstract: Gastric cancer (GC) is a common tumour that affects humans worldwide, is highly malignant and has a poor prognosis. Small extracellular vesicles (sEVs), especially exosomes, are nanoscale vesicles released by various cells that deliver bioactive molecules to recipient cells, affecting their biological characteristics, changing the tumour microenvironment and producing long-distance effects. In recent years, many studies have clarified the mechanisms by which sEVs function with regard to the initiation, progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 191 publications
0
47
0
Order By: Relevance
“…Caspase 9 is an important protein essential to intrinsic apoptosis pathway function [ 61 ]. Data presented by our study suggests that EVs released from HAdV3-infected A549 cells bear stress and apoptotic markers which were evident in the cell viability and morphology after infection and that HAdV3-induced death in A549 cells could be chiefly through an intrinsic apoptosis program rather than extrinsic [ 60 62 ]. We assessed another important EV surface molecule that is commonly found on certain cell types but is crucial for distinguishing EVs' parent cells.…”
Section: Discussionmentioning
confidence: 99%
“…Caspase 9 is an important protein essential to intrinsic apoptosis pathway function [ 61 ]. Data presented by our study suggests that EVs released from HAdV3-infected A549 cells bear stress and apoptotic markers which were evident in the cell viability and morphology after infection and that HAdV3-induced death in A549 cells could be chiefly through an intrinsic apoptosis program rather than extrinsic [ 60 62 ]. We assessed another important EV surface molecule that is commonly found on certain cell types but is crucial for distinguishing EVs' parent cells.…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al demonstrated that DCA-activated macrophages could secrete exosomes to carry miR-30a-5 to gastric epithelial cells, thereby promoting gastric IM by targeting FOXD1 [ 51 ]. It was found that IM might arise from spasmolytic polypeptide-expressing metaplasia (SPEM) [ 52 ]. DCA could promote SPEM by macrophage-derived exosomes [ 53 ].…”
Section: Mechanism Of Gastric Im Induced By Bile Acidmentioning
confidence: 99%
“…The varying sizes, content, function, and cellular origin of exosomes contributes to their heterogeneity [13]. Although our understanding of exosome biogenesis, release, uptake, and function are not completely clear [23][24][25][26], exosome-focused research remains topical and extensive, which can be ascribed to the potential capability of exosomes in the diagnosis and treatment of various diseases, including neurodegeneration [27], metabolic disorders [28], cardiovascular dysfunction [29], and cancer [30]. Furthermore, exosomes have been widely used in targeted drug delivery through surface engineering techniques, which provides effective strategies for diagnosis and treatment, especially in cancer [31].…”
Section: The Biogenesis Of Exosomesmentioning
confidence: 99%